2022
DOI: 10.3389/fcell.2022.903436
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Reduces Neuroinflammation to Provide Retinal Ganglion Cell Neuroprotection in the Retina Axotomy Model

Abstract: Neuroinflammation is a critical and targetable pathogenic component of neurodegenerative diseases, including glaucoma, the leading cause of irreversible blindness. Valproic acid has previously been demonstrated to reduce neuroinflammation and is neuroprotective in a number of experimental settings. To determine whether valproic acid can limit retinal neuroinflammation and protect retinal neurons we used an ex vivo retina explant (axotomy) model to isolate resident glial responses from blood-derived monocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In murine models of NTG, VPA has been found to decrease oxidative stress and enhance RGC survival through a pathway associated with ERK [311]. Additionally, a recent Swedish study using retina explant models suggested that VPA possesses anti-inflammatory properties by reducing the expression of pro-inflammatory cytokines and attenuating microglial changes, highlighting its potential as an anti-neuroinflammatory drug in retinal diseases [312]. A randomized controlled trial assessing the effectiveness of VPA in glaucoma patients reported an improvement of visual acuity among patients with advanced glaucoma [313].…”
Section: Other Antioxidant Moleculesmentioning
confidence: 99%
“…In murine models of NTG, VPA has been found to decrease oxidative stress and enhance RGC survival through a pathway associated with ERK [311]. Additionally, a recent Swedish study using retina explant models suggested that VPA possesses anti-inflammatory properties by reducing the expression of pro-inflammatory cytokines and attenuating microglial changes, highlighting its potential as an anti-neuroinflammatory drug in retinal diseases [312]. A randomized controlled trial assessing the effectiveness of VPA in glaucoma patients reported an improvement of visual acuity among patients with advanced glaucoma [313].…”
Section: Other Antioxidant Moleculesmentioning
confidence: 99%
“…In murine models of NTG, VPA has been found to decrease oxidative stress and enhance RGC survival through a pathway associated with ERK [302]. Additionally, a recent Swedish study using retina explant models suggested that VPA possesses anti-inflammatory properties by reducing the expression of proinflammatory cytokines and attenuating microglial changes, highlighting its potential as an antineuroinflammatory drug in retinal diseases [303]. A randomized controlled trial assessing the effectiveness of VPA in glaucoma patients reported an improvement in visual acuity among patients with advanced glaucoma [304].…”
Section: Other Antioxidant Moleculesmentioning
confidence: 99%
“…The elucidations of such mechanisms could be crucial. The experimental inhibition of retinal HDAC activity with specific agents such as valproic acid (VPA) has been proven to be successful as neuroprotective treatment [ 41 , 42 , 43 , 44 , 45 ].…”
Section: Epigenetic Modifications In Glaucomamentioning
confidence: 99%
“…Specifically, VPA is an inhibitor of the activity of HDAC enzymes, particularly HDAC1, and is involved in the regulation of gene expression by modifying the acetylation status of histones [ 44 , 45 ].…”
Section: Epigenetic Modifications In Glaucomamentioning
confidence: 99%